AN ANALYSIS OF THE MAIN CHARACTERS’ CONFLICTS IN OSCAR WILDE’S NOVEL “THE IMPORTANCE OF BEING EARNEST” - Asrul Hasby; Sudirman Sudirman (Mandala, 2019)
This study focuses on the Earnest Worthing’s and Algernon’s characteristics toward the conflicts in ‘Oscar Wilde’s Novel in titled “The Importance of Being Earnest”. It aims to describe characters’ of Earnest Worthing and Algernon. The method used in this study was qualitative with textual analysis based on Moleong (2000). The results of this study showed that the main character’s of the Earnest Worthing is very kind man because he wanted to do everything for the one that he love namely Gwendolen, he is really friendly as well and Algernon is a man who never been serious in doing something but he is a romantic person. Their characters were taken Based on conflicts which were happened in the novel of Oscar Wilde in titled “The Importance of Being Earnest” and also supported by some experts such as; Wilde (1959), Robert (2003), and Meyer (1990).